PHP for Absolute Beginners - Lengstorf, Jason. (Apress : Imprint: Apress, 2014)
PHP is a server-side scripting language that enables you to develop dynamic sites that engage users in ways that are simply not possible using only HTML and CSS. PHP for Absolute Beginners takes a practical approach to teaching you how to build dynamic content for your website using PHP. You’ll quickly get started with practical PHP projects, learning how to build a dynamic image gallery. By the end of the book you’ll will have developed a personal blog complete with a password protected admin module. PHP for Absolute Beginners won't swamp you with every detail of the full PHP language up front – instead, you’ll be introduced to a small, versatile subset of PHP and learn to use it creatively to develop dynamic web sites. In the process you will learn to use variables, control structures, functions, and objects to your advantage. You will learn how to plan and create databases and how to organize your PHP scripts beautifully. At the end of the book, you will be a confident PHP user, ready to take the next steps in creating great websites.